Leading in Adverse Times: Lessons Learned by School Leadership in Spain During the COVID-19 Challenge. - Cruz-González, Cristina; Jiménez-García, José Daniel; Cadenas-Sánchez, Cristina; López-Fernández, Iván; Gil-Espinosa, Francisco Javier (Taylor & Francis, 2026)
This mixed-methods study examines 387 Spanish school principals during COVID-19. It shows how their roles expanded to include health coordination, emotional support, and digital adaptation. Quantitative data were analyzed with SPSS using descriptive statistics and Pearson correlations, and qualitative data were examined using grounded-theory-informed coding. The findings highlight adaptive leadership in fostering resilience through restructuring and collaboration. They also show how principals balanced multiple duties and indicate the need for reforms to strengthen crisis management capacity. The study identifies three measures: crisis protocols, permanent health liaison roles, and digital leadership training, offering lessons from Spain for international leadership debates.
The authors acknowledge financial support from the Junta de Andalucía through the KEY Project “School Leadership as a Value of Educational Quality” [Grant PIV-030/22], which contributed to the development of this study.
Keywords: Directores de centros docentes; Alfabetizacion digital; School principals; Crisis management; Leadership; Digital competencies; Pandemic